2009
DOI: 10.1021/jp805976a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Benzene to Copper in CuHY Zeolite

Abstract: Adsorption of benzene to copper-exchanged Y zeolites has been studied employing Fourier transform infrared spectroscopy and QM/MM calculations. Experimentally, both Cu(I) and Cu(II)-Y zeolites were used as adsorbents. Benzene adsorption was observed on both copper and Brønsted acid sites, but the copper site is preferred. The FTIR spectra show the activation of the ν 13 in-plane ring stretching mode at 1471 and 1479 cm -1 for Cu and Brønsted sites, respectively. With respect to the gas-phase value, Cu sites ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 83 publications
1
33
1
Order By: Relevance
“…However, the 3670 cm À1 OH band in FAU zeolite is shifted by benzene to one band at 3450 (Dm = 220 cm À1 ) [33]. Evidently, in this case the wavenumber of the shifted OH band is too high in order Fermi resonance to occur.…”
Section: Changes In the Oh/od Regions At Low And Medium Benzene Covermentioning
confidence: 89%
“…However, the 3670 cm À1 OH band in FAU zeolite is shifted by benzene to one band at 3450 (Dm = 220 cm À1 ) [33]. Evidently, in this case the wavenumber of the shifted OH band is too high in order Fermi resonance to occur.…”
Section: Changes In the Oh/od Regions At Low And Medium Benzene Covermentioning
confidence: 89%
“…zeolites, alumina, aluminosilicalites or higher-order oxides are attractive materials in numerous applications in catalysis. Previous research has shown that those materials play a significant role in the separation and stabilization of various reactive intermediates as atoms, radicals, radical ions, and clusters [1][2][3][4][5][6][7]. Studies of such intermediates are very important for a better understanding of the mechanisms of chemical reactions in polymerization, heterogeneous catalysis, photochemistry, and radiation chemistry and biology.…”
Section: Introductionmentioning
confidence: 99%
“…The latter spectrum was assigned to the radical CH 3 Ċ α HC 6 an averaging due to the free rotation usually occurring along the >C α -CH 3 bond in this type of radicals [42]. The anisotropy of the methyl coupling was somewhat averaged by the rotation to become axially symmetric.…”
mentioning
confidence: 98%
“…The difference between samples could be attributed not only to a difference in the copper content, but also to the difference in their textural properties. Archipov et al [34] studied the adsorption of benzene in copper-exchanged Y zeolites, using Fourier transform infrared spectroscopy; the authors found that benzene adsorbed on both copper and brønsted acid sites of the zeolite, but preferentially on copper site. With the assumptions of a similar behavior for the toluene-zeolite system, it can be expected that the copper-exchanged samples exhibit higher capacities of adsorption in comparison to the NaX zeolite.…”
Section: Xps Analysesmentioning
confidence: 99%